1992
DOI: 10.1051/agro:19920708
|View full text |Cite
|
Sign up to set email alerts
|

Influence de la température sur la croissance in vitro d'hyphomycètes entomopathogènes

Abstract: Résumé — L'influence de la température sur la croissance in vitro des principales espèces d'hyphomycètes entomopathogènes a été étudiée avec 31 isolats fongiques : 3 souches de Beauveria bassiana (Balsamo) Vuillemin, 3 souches de B brongniartii (= tenella) (Saccardo) Petch, 8

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
54
1
4

Year Published

1996
1996
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 10 publications
10
54
1
4
Order By: Relevance
“…Therefore, the combined effect of high temperature and low water availability on vegetative growth of B. bassiana was studied. Variations in isolate response to high temperature and low water availability conditions were observed, as anticipated from previous reports (11,12,13). Hallsworth and Magan (16), and Sivasankaran et al (44) reported that B. bassiana isolates require high levels of water activity in the surrounding medium for germination.…”
Section: Discussion "Two-stage" Cultivation Methodssupporting
confidence: 85%
See 2 more Smart Citations
“…Therefore, the combined effect of high temperature and low water availability on vegetative growth of B. bassiana was studied. Variations in isolate response to high temperature and low water availability conditions were observed, as anticipated from previous reports (11,12,13). Hallsworth and Magan (16), and Sivasankaran et al (44) reported that B. bassiana isolates require high levels of water activity in the surrounding medium for germination.…”
Section: Discussion "Two-stage" Cultivation Methodssupporting
confidence: 85%
“…bassiana has been studied (7,12,13,22,44). A temperature of 25°C was reported optimum for B. bassiana by Fargues et al…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both species were isolated from substrates collected in typical vector habitats, and all isolates proved to be highly active against T. infestans at favorable conditions of moisture. M. anisopliae is considered a mildly thermophilic species in comparison to B. bassiana (Fargues et al 1992, Ouedraogo et al 1997, and the higher incidence of this pathogen in this study may be related to the tropical climate in Central Brazil.…”
Section: Discussionmentioning
confidence: 71%
“…Composition of the substrate or the diversity and number of microorganisms may affect survival and development of entomopathogenic fungi. Extreme temperature conditions, especially those exceeding 35ºC, may injure or kill fungi (Fargues et al 1992, Ouedraogo et al 1997, Luz & Fargues 1997. Such elevated temperatures can easily be achieved in closed rooms such as poultry houses, barns or other unventilated spaces after prolonged exposure to sunlight.…”
Section: Discussionmentioning
confidence: 99%